Analysis of Bad Credit Problems in the Savings and Loans Cooperative Unit of SMK Negeri 9 Medan - Perkasa, Ripho Delzhy; Rahmah, Aulia; Zidane, Ramandha (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This article aims to find out the problem of bad credit at the cooperative savings and loan unit of Smk Negeri 9 Medan. This research was conducted using survey, interview and observation techniques regarding the problem of bad credit at the SMK Negeri 9 Medan cooperative. The results obtained stated that the savings and loan unit at the Smk Negeri 9 Medan cooperative experienced bad credit problems. The problems experienced by the Smk Negeri 9 Medan cooperative savings and loan unit were caused by members being late in making payments every month. The payment was late because the salaries of the members, namely the teachers at SMK Negeri 9 Medan, were delayed in leaving. The conclusion of this research is to discuss the problem of bad credit that occurs in the cooperative savings and loan unit of Smk Negeri 9 Medan which is caused by late members' salaries leaving.